Видові особливості дієслів лексико-семантичної групи зі значенням звучання - Чубань, Т.В.; Левченко, Т.М. (Інститут літератури ім. Т.Г. Шевченка НАН України, 2009)
В статье исследован вопрос о значении наблюдения над глаголом при изучении украинского языка, выделены основные аспекты исследования перфективации глаголов в современном украинском языке. Охарактеризовано видовые особенности глаголов лексико-семантической группы со значением звучания. Описано параметры перфективации глаголов, которые называют действия, которые выражают произвольные и активно образованные кем-то или чем-то звуки. Выделено и охарактеризовано лексико-семантическую группу вербальных глаголов украинского языка со значением звукового проявления, которые имеют свои особенности в соединении с приставками как реализаторами словообразовательно-грамматической и грамматической функции. Выводы подтверждены примерами. The article studies the importance of observing the verb in learning the Ukrainian language, and emphasizes the main aspects in the study of verbal perfectivation within the modern Ukrainian language. The authors characterize aspectual peculiarities of verbs belonging to the lexico‐semantical group that denotes sounding. They also describe parameters of verbal perfectivation for verbs denominating action that denote sounds involuntary or actively uttered by someone or something. The article points out and characterizes the lexico‐semantical group of vocal verbs in the Ukrainian language denoting vocality, which have their specific features in their ability to combine with prefixes as elements implementing the word‐building and grammatical functions. Such grounding of the issue is supported by numerous examples provided.